PERAN MEDIASI BRAND IMAGES PADA HUBUNGAN ANTARA SOCIAL MEDIA MARKETING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA WISATAWAN YANG BERBELANJA DI KRISNA TOKO OLEH-OLEH KHAS BALI) - Syarif Hidayatullah; Surya Wahyuning Tiyas; Stella Alvianna; Anisa Zuhria Sugeha; Ike Kusdyah Rachmawati (Jurnal Pariwisata Pesona, 2021)
Online promotion is currently an alternative solution in marketing the products produced because, at this time, all community activities are carried out online in online media such as social media, television, or digital catalogs that display all products offered attractively and interactively people to see and observe them. The variables in this study are Social Media Marketing, product quality, brand images, and purchasing decisions. The population in this study is people who are or have visited the Krisna Bali Souvenir Shop with a total sample of 160 people. The results of this study are Social Media Marketing does not affect brand images, product quality affects brand images, brand images affect purchasing decisions, Social Media Marketing affects purchasing decisions through brand images, and product quality does not affect purchasing decisions through brand images.